PERAN PEMERINTAH DALAM MENANGGULANGI KENAKALAN REMAJA DI DESA KABORI DISTRIK KEMBU KABUPATEN TOLIKARA - Enembe, Wekiles; Lesawengan, Lisbeth; Mumu, Rudy (HOLISTIK, Journal Of Social and Culture, 2018)
The problem of juvenile delinquency until recently can be said to have become a social problem that needs to be faced by the Government, society and the family. The reason is because the rate of juvenile delinquency which lately occurred already lead to criminal action. Now many people recently with the occurrence of a brawl between the Kampong teenagers leading to the Act of breaking the law, even the passing of youth and teenagers.The problem of juvenile delinquency already penetrated up to the countryside as well as in the Kabori village of District Kembu Tolikara Regency.Â  Rising juvenile delinquency happening lately so that the authorities of the village, giving considerable attention because often make a scene and have to deal with police, the altercation between the village, drinking alcohol, smoking and drugs, inhaling Aibon glue and free sex. Such action is very troubling the Government villages, in particular the community or family.The inclusion of negative influences into a life community Kabori village order is slowly but surely starting to life gnaw community Kabori village order, because his young generation began to leave his ancestor's habits were considered old-fashioned and outdated and they would follow the new lifestyle that comes from the outside. It needs to be a more serious handling of the local government in particular Government Kabori village.Keywords : delinquency, juvenile, teenagers